MANAJEMEN LEAN PADA LAYANAN KEMOTERAPI ANAK RAWAT INAP DI RUMAH SAKIT CIPTO MANGUNKUSUMO - Teny Tjitra Sari; Andreasta Meliala; Firman (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2019)
Background: Cancer in children has high morbidity and mortality. Retinoblastoma is the most common solid tumor in children at the Cipta Mangunkusumo Hospital (RSCM). Chemotherapy is one of the therapeutic modalities, interdisciplinary and many procedures. Lean management continuously reduces waste and improves work flow. Objective: This study used lean management to determine the efficiency of health care in teaching hospital. Methods: Action research was conducted at RSCM. Sampling by purposive sampling that represents the role in the flow of the service process. The observation guide uses cycle time observation sheets, value-added analysis sheets, waiting time and lead time. The waste found is listed in the DOWNTIME matrix. Observations were made on inpatient chemotherapy services for children and then a diagnosis was made using Value Stream Mapping. The Kaizen team consisted of pharmacists, nurses, doctors doing a plan-do-study-action, prepared an intervention plan, and conducted post-intervention observations. The 5S method is used to improve service flow. Results: In this study, patients with retinoblastoma in class III in patient ward included were 7 patients in the pre-intervention group and 16 patients in the postintervention group. Major decreases in lead time happened in the subprocesses of ordering chemotherapy (75%), decision-making of chemotherapy administration (55%) and filling of the resume (41%). Lead time process in chemotherapy administration for retinoblastoma changed from 48 hours, 36 minutes (more than 2 days) to 38 hours, 38 minutes (1.6 days or less than 2 days). The efficiency of the process was measured using value added ratio which showed changes from 33% to 37%. Conclusion: Lean management applied in the process of chemotherapy administration in the inpatient wards increased the efficiency of the process.